2016
DOI: 10.1111/epi.13502
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term exposure and safety of lacosamide monotherapy for the treatment of partial‐onset (focal) seizures: Results from a multicenter, open‐label trial

Abstract: SUMMARYObjective: To assess long-term use and safety of lacosamide (LCM) ≤800 mg/day monotherapy in patients with partial-onset seizures (POS) enrolled previously in a historical-controlled, conversion-to-monotherapy study (SP902; NCT00520741). Methods: Patients completing or exiting SP902 with LCM as monotherapy or as adjunctive therapy were eligible to enter this 2-year open-label extension (OLE) trial (SP904; NCT00530855) at a starting dose AE100 mg/day of their final SP902 dose. Investigators could adjust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…12 In this trial, TEAEs of headache and nasopharyngitis were the most common, similar to results of previous trials of lacosamide monotherapy. 2,8,13,14 The low doses of lacosamide (median modal dose of 200 mg/day) used in this trial may explain the very low rates of dizziness and fatigue reported (<2% of all patients each), and why no cognitive disorders were reported. There were three "other significant TEAEs" that were all cardiac-related.…”
Section: Discussionmentioning
confidence: 97%
“…12 In this trial, TEAEs of headache and nasopharyngitis were the most common, similar to results of previous trials of lacosamide monotherapy. 2,8,13,14 The low doses of lacosamide (median modal dose of 200 mg/day) used in this trial may explain the very low rates of dizziness and fatigue reported (<2% of all patients each), and why no cognitive disorders were reported. There were three "other significant TEAEs" that were all cardiac-related.…”
Section: Discussionmentioning
confidence: 97%
“…The fifty-three case series ( Guilhoto et al, 2010 ; García-Morales et al, 2011 ; Gavatha et al, 2011 ; Höfler et al, 2011 ; Maschio et al, 2011 ; Casas-Fernández et al, 2012 ; Heyman et al, 2012 ; Flores et al, 2012 ; Harden et al, 2012 ; Husain et al, 2012 ; Song et al, 2012 ; Giorgi et al, 2013 ; Kamel et al, 2013 ; Li et al, 2013 ; Villanueva et al, 2013 ; Garcés et al, 2014 ; Grosso et al, 2014 ; Kellinghaus et al, 2014 ; Kim et al, 2014 ; Rosenfeld et al, 2014 ; Stephen et al, 2014 ; Wechsler et al, 2014 ; Yorns et al, 2014 ; Andrade-Machado et al, 2015 ; Geffrey et al, 2015 ; IJff et al, 2015 ; Lattanzi et al, 2015 ; Runge et al, 2015 ; Villanueva et al, 2015 ; Arkilo et al, 2016 ; Borzì et al, 2016 ; Miskin et al, 2016 ; Vossler et al, 2016 ; Baulac et al, 2017 ; Bottcher et al, 2017 ; Brenner et al, 2017 ; Rinesalo et al, 2017 ; Sepúlveda-Sánchez et al, 2017 ; Svendsen et al, 2017 ; Arabi et al, 2018 ; Baker et al, 2018 ; Munoz-Lopetegi et al, 2018 ; Ngampoopun et al, 2018 ; Rosati et al, 2018 ; Rudà et al, 2018 ; Samarasekera et al, 2018 ; Sanmartí-Vilaplana et al, 2018 ; Toledo et al, 2018 ; Kleist et al, 2019 ; Ruegger et al, 2019 ; Chiara Del et al, 2019 ; Hmaimess et al, 2020 ; Ruda et al, 2020 ; Zhao et al, 2021 ) included totally 6,107 patients aged 6 months to 95 years, with thirteen studies inv...…”
Section: Resultsunclassified
“…31 In a 2-year follow-up of 322 patients with partial-onset seizure, lacosamide monotherapy produced a favorable outcome and safety profiles. 30 Brivaracetam increases the binding affinity of the synaptic vesicle protein SV2A by 10-fold more than levetiracetam. It was approved by the Korean FDA in 2019, and has been available for prescribing as an additional treatment in patients with focal seizure since 2020.…”
Section: Additional Drugmentioning
confidence: 99%
“…Lacosamide, phenobarbital, phenytoin, pregabalin, vigabatrin, and zonisamide can be considered as the next step in the process. Lacosamide 30 has been used as a single drug for controlling the first focal seizure in Europe and the United States, but has only been approved as an additional antiepileptic drug for focal seizure in Korea. 31 In a 2-year follow-up of 322 patients with partial-onset seizure, lacosamide monotherapy produced a favorable outcome and safety profiles.…”
Section: Antiepileptic Drug Selection According To Seizure Typesmentioning
confidence: 99%
See 1 more Smart Citation